Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 5 - 5.3 - Properties of Logarithms - 5.3 Exercises - Page 386: 74



Work Step by Step

$2[3\ln x-\ln(x+1)-\ln(x-1)]=2[\ln x^3-\ln(x+1)-\ln(x-1)]=2\ln\frac{x^3}{(x+1)(x-1)}=2\ln\frac{x^3}{x^2-1}=\ln(\frac{x^3}{x^2-1})^2=\ln\frac{x^6}{(x^2-1)^2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.